MEASURING ALTRUISM AMONG YOUTH IN MALAYSIA: AN INSTRUMENT DEVELOPMENT USING THE EXPLORATORY FACTOR ANALYSIS - Awang, Salwa Amirah; Muhammad, Fidlizan; Mohamad Said, Aishah; Ibrahim, Rahimah (Jurnal ’Ulwan, 2023)
Altruism is the willingness of a person to act for the benefit and interest of others without any implicit motives which is regarded as the highest level of akhlaq in Islam especially in Muamalah. Realizing its importance, this paper seeks to design an instrument to measure the value of altruism among youth in Malaysia using the quantitative survey method. The proposed instrument comprises of two main components which are the altruism belief and the altruism behaviour. The first component was constructed by basing on the key elements of altruism found in the literature and the second component was adopted from the Self Report Altruism Scale (SRA) with some elements had been modified to suit the Malaysian context. The sampling involved in this study was 198 students of a polytechnic in Malaysia by using the cluster sampling with the ratio of 30:70 (30% Commerce students and 70% Engineering students) of the total enrollment. The data was then analyzed using the reliability analysis and the Exploratory Factor Analysis (EFA). The value of Cronbach Alpha was 0.935 for all components, 0.864 for the first component and 0.937 for the second component. The EFA result showed that almost all items have proven a sound validity construct with loadings more than 0.5 and an item with a loading less than 0.3 was removed. This study contributes to the formation of a sound instrument to capture a comprehensive value of altruism especially among youth in the local setting.